Withholding Versus Continuing Angiotensin-Converting Enzyme Inhibitors or Angiotensin II Receptor Blockers Before Noncardiac Surgery: An Analysis of the Vascular Events in Noncardiac Surgery Patients Cohort Evaluation Prospective Cohort. Issue 4 (August 2017) - Roshanov, P. S.; Rochwerg, B.; Patel, A.; Salehian, O.; Duceppe, E.; Belley-Côté, E. P.; Guyatt, G. H.; Sessler, D. I.; Le Manach, Y.; Borges, F. K.; Tandon, V.; Worster, A.; et al.
Abstract : (Abstracted from Anesthesiology, 126(1):16–27, 2017) The purpose of this international prospective cohort study was to assess the effect of withholding angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) on the risk of 30-day composite outcome of all-cause death, myocardial injury following noncardiac surgery (MINS), and stroke, as well as to determine the relationship between withholding ACEIs/ARBs and perioperative hypotension.